2015
DOI: 10.1007/s11136-015-1011-x
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and construct validity of the Adult Social Care Outcomes Toolkit for Carers (ASCOT-Carer)

Abstract: BackgroundThe ASCOT-Carer is a self-report instrument designed to measure social care-related quality of life (SCRQoL). This article presents the psychometric testing and validation of the ASCOT-Carer four response-level interview (INT4) in a sample of unpaid carers of adults who receive publicly funded social care services in England.MethodsUnpaid carers were identified through a survey of users of publicly funded social care services in England. Three hundred and eighty-seven carers completed a face-to-face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
125
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(134 citation statements)
references
References 49 publications
9
125
0
Order By: Relevance
“…by telephone or face‐to‐face) because it may result in systematic bias due to social desirability bias or other factors (Bowling, ). In another study based on the sample analysed here, it was found that carers interviewed by telephone reported lower quality of life compared to those who completed the interview face‐to‐face (Rand et al, ).…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…by telephone or face‐to‐face) because it may result in systematic bias due to social desirability bias or other factors (Bowling, ). In another study based on the sample analysed here, it was found that carers interviewed by telephone reported lower quality of life compared to those who completed the interview face‐to‐face (Rand et al, ).…”
Section: Methodsmentioning
confidence: 80%
“…Carer care‐related quality of life is an overarching outcome indicator, which captures aspects of quality of life valued by carers and that also may be affected by long‐term care support (e.g. carer support groups, short‐term breaks) (Netten et al, ; Rand & Malley, ; Rand et al, ). The focus on carers’ quality of life outcomes reflects the wider repositioning of carers as co‐clients whose own needs and outcomes should be considered by long‐term care services (Rand & Malley, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a validated instrument for measuring CRQoL of informal unpaid carers who care for adults with a variety of long‐term conditions, disability or problems related to old age (Malley, Fox, & Netten, ; Rand, Malley, Netten, & Forder, ; Smith, Fox, & Holder, ). ASCOT‐Carer covers seven domains: spending time on valued or enjoyable activities, having control over daily life, looking after oneself, feeling safe, having social contact, having space and time to be oneself and feeling encouraged and supported in the caring role (Rand et al, ). Each domain has four response categories from ‘no needs' to ‘high levels of needs'.…”
Section: Methodsmentioning
confidence: 99%